2016
DOI: 10.1039/c5cy01524c
|View full text |Cite
|
Sign up to set email alerts
|

Active phase distribution changes within a catalyst particle during Fischer–Tropsch synthesis as revealed by multi-scale microscopy

Abstract: A new combination of three chemical imaging methods has been developed and applied to fresh and spent co-based Fischer–Tropsch catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 71 publications
9
52
0
Order By: Relevance
“…This instrument provides the opportunity to carry out unique experiments, which are complimentary to the research performed at synchrotron radiation facilities. [16] Furthermore, during FTS at different conditions (pressure and H 2 /CO ratio) no cobalt re-oxidation was observed, which is in line with earlier reports [35][36][37] from our research group, confirming that oxidation of the cobalt is not a main deactivation route for FTS, leaving sintering and coke formation as main reasons for the detrimental activity over time for Cobased FTS catalyst. Such experiments are difficult to perform at synchrotrons due to the limited time available during granted beamtimes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This instrument provides the opportunity to carry out unique experiments, which are complimentary to the research performed at synchrotron radiation facilities. [16] Furthermore, during FTS at different conditions (pressure and H 2 /CO ratio) no cobalt re-oxidation was observed, which is in line with earlier reports [35][36][37] from our research group, confirming that oxidation of the cobalt is not a main deactivation route for FTS, leaving sintering and coke formation as main reasons for the detrimental activity over time for Cobased FTS catalyst. Such experiments are difficult to perform at synchrotrons due to the limited time available during granted beamtimes.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, no re-oxidation of the cobalt metal nanoparticles was observed in any of the FTS experiments performed at different pressures (1 and 5 bar), and H 2 /CO ratios (0.5 and 2), which agrees with previous studies from our research group that indicate that re-oxidation is not observed during the activation or deactivation stages of a Co/TiO 2 FTS catalyst. [35][36][37]…”
Section: Long-term Fts Reaction Experimentsmentioning
confidence: 99%
“…Furthermore,t he fact that this intensity is present both in clustered data, and in the carbon K-edge-jump intensity maps plotted in Figure 4, tells us that these species are not only chemically different, but there is also more carbon present where these species are located. [27] Additionally,i nF igure 4as mall feature at 288.3 eV emerges inwards,f rom the particle shell to the particle core, which is continued at 47 hi nF igure 4. Thef act that these spots merge after 51.5 hcan indicate the redistribution of cobalt, which is linked to the formation of carbon in Figure 4, consistent with previous findings from our group.…”
Section: Angewandte Chemiementioning
confidence: 93%
“…While the literature is imbued with proposed deactivation mechanisms, [5,10,11] the equally interesting catalyst activation period is often overlooked. [26][27][28][29] Operando characterization studies can greatly advance our knowledge of working catalyst systems providing nanoscale chemical information on both the organic (products and reaction intermediates) and the inorganic (metal and support) constituents of the catalyst material under operating conditions (i.e., high temperatures and pressures and reactants). [12,14,15] The complexity of the FTS process is also captured in the myriad of proposed deactivation mechanisms,w hich are generally related to the conversion of the active phase, considered as metallic cobalt, into an inert phase.F or example,cobalt reoxidation or carburization, [16,17] the formation of support oxide-cobalt species occurring through strong metal-support interactions (SMSI), [8,18,19] the loss of active cobalt surface area arising from crystalline growth (i.e., metal sintering), [11,[20][21][22] and finally fouling for example by hydrocarbon deposition in the form of various carbon species formed at the cobalt surface.…”
mentioning
confidence: 99%
“…A specific example of a catalyst system where significant efforts have been made to achieve industrial conditions during lab experiments [3][4][5][6][7][8] is the Fischer-Tropsch synthesis (FTS), which is a heterogeneous surface polymerization reaction. [5,[9][10][11][12] It hydrogenates synthesis gas, a mixture of H 2 and CO, into longchain hydrocarbons over supported metal catalysts, thereby producing high-purity chemicals and fuels from sources other than crude oil.…”
Section: Introductionmentioning
confidence: 99%